Kejadian Dismenorhoe pada mahasiswi dengan anemia - Machmud, Azrida; Sharief, Suchi Avnalurini; Thamrin, Halida (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2018)
For children and adolescent girls found many health problems, especially anemia. In women with iron deficiency anemia, the amount of menstrual blood is also more. Most women do not feel the symptoms at the time of menstruation, but some feel heavy in the pelvis or feel pain (dysmenorrhoea). Various studies have shown that the incidence of dysmenorrhoea is still quite high, those who experience severe dysmenorrhoea after taking the drug should rest and it is recommended to limit even leave the school or work for 1-3 days in a month which would certainly be detrimental to women in the activity, especially in young women who are in a period of growth and development. The purpose of this study to determine the relationship between anemia with dismenorhoe incident. The approach taken in this research is quantitative. This type of research used surveyive design with cross sectional approach. In this research the sampling method using Random Sampling technique. The results showed a significant relationship between anemia with the incidence of dysmenorrhoea in UMI midwifery students where the results of Chi Square test of 9,737 with p-value 0.0001 <0,05. It can be concluded that anemia can cause dysmenorrhoea in young women, so the need to increase knowledge about nutrition for young woman to prevent the happening of anemia.